2014
DOI: 10.4103/0971-5851.133707
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of BCR-ABL transcript variants in patients with chronic myeloid leukemia: Their correlation with presenting features, risk scores and response to treatment with imatinib mesylate

Abstract: Context:The exact role of the different transcript variants of BCR-ABL in the pathogenesis of chronic myeloid leukemia (CML) and their impact on prognosis is yet to be definitely enumerated.Aims:In this study, we have tried to correlate the presenting features, risk scores and treatment response with the BCR-ABL variants detected in our patients.Settings and Design:A cross-sectional unicentric hospital-based study on 80 patients diagnosed to have CML by bone marrow cytogenetics and confirmed by reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
2
7
1
1
Order By: Relevance
“…In our study, the frequencies of b3a2 and b2a2 fusion transcript variants were found to be 60.97% and 39.02% respectively which corresponded with the studies done in this part of our country (b3a2 56.25%, b2a2 41.25%) 17 . Kagita et al ., 2018 in their study observed 63.53% of CML patients were having b3a2 and 36.36% b2a2 transcript variants and another Indian study noted the frequencies of b3a2 and b2a2 to be 66.82% and 28.84% respectively 18 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the frequencies of b3a2 and b2a2 fusion transcript variants were found to be 60.97% and 39.02% respectively which corresponded with the studies done in this part of our country (b3a2 56.25%, b2a2 41.25%) 17 . Kagita et al ., 2018 in their study observed 63.53% of CML patients were having b3a2 and 36.36% b2a2 transcript variants and another Indian study noted the frequencies of b3a2 and b2a2 to be 66.82% and 28.84% respectively 18 .…”
Section: Discussionsupporting
confidence: 90%
“…After the confirmation of the diagnosis of CML, 35 patients were in chronic phase (CP), 21 were in accelerated phase (AP) and 6 were in blast crisis (BC). The Sokal score was calculated following the standard method for each patient before starting imatinib therapy 17,20,22 .…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in India and Bulgaria calculated the ratio of the two major transcripts of M-BCR region e14a2:e13a2 to be 1.3:1, which is almost in agreement to the ratio observed in the present study [ 13 , 24 ]. However, studies from our local population represent comparatively higher ratio of the two transcripts than reported here [ 9 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned, several studies have shown the importance of BCR-ABL1 transcripts in treatment response, and contradictory results have been demonstrated in different studies that analysed expression of BCR-ABL1 transcript variants, showing an advantage for patients with b3a2. Patients with b3a2 are more likely to achieve favourable molecular major response (MMR) because they may have lower tyrosine kinase activity than those with b2a2, and thus be more sensitive to imatinib treatment (26)(27)(28)(29)(30). In an apparent contradiction, de Lemos et al reported that b2a2 patients had better MMR at 6 months (31), whereas another study showed no significant differences between patients with b3a2 and b2a2 in MMR at 6 months (32).…”
Section: Resultsmentioning
confidence: 99%